Rancang Bangun Mesin Pelangsiran Material Konstruksi Tower Transmisi Sistem Crane Pulley dengan Kapasitas Maksimal 250 kg - Mukhamad, Alaya Fadlu Hadi; Darmanto, Seno; Haqni, Firdaus Kurniawan (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2022)
Material shredders are used in construction projects to move materials from the starting point to the intended point. This trimming machine uses a type or system of crane pulley. In the world of construction, it can rarely be used in various terrains, whether flat terrain, valley terrain, or hilly terrain. Therefore, this paper aims to ensure that the process of upgrading / transferring the construction material of the 150 kV transmission tower can run well on flat terrain to difficult terrain such as valleys and hills based on several consideration factors. The design process of the material shredder consists of three stages, namely design, tool making, and tool testing. The design process consists of several stages, namely field review and the availability of supporting systems and raw materials. The fabrication process, carries out the assembly of materials that are already available by the predetermined design. The process of testing the tool, using the test method directly in the field so that the data presented is real loading data. The material drill engine can be used well in the field with a maximum carrying capacity of 250 kg with the highest effective tool capacity of 12,424kg/hour and fuel sed as much as 0.91 liters/hourKeywords : Design and Construction, Solidworks, Material Transfer Tool, Shifting Machine, Material Mover